Specificity and Selectivity in Galacto-Oligosaccharide Synthesis Reactions Catalyzed by 13-Galactosidases - Sony Suwasono (Indonesian Food and Nutrition Progress, 2003)
Galacto-oligosaccharides (GalOS) are known as functional foods or prebiotics, and they have potential functions as efficient growth factors for Bifidobacteria and Lactobacilli. The Bifidobacteria participate in human digestion by improving metabolism as well as preventing the growth of putrefactive bacteria. The Bifidobacteria also posses anticarcinogen and anticholesterolaemic properties. In order to give the availability of GalOS in human diet, it will be necessary to manufacture synthetic GalOS using a simple method This research is an attempt to synthesize GalOS by means of high concentrations of galactose or lactose as the substrate employing b-galactosidases (EC 3. 2. 1. 23) from Aspergillus oryzae, and Bacillus circulans. The characteristics of synthesis reaction of GalOS with these enzymes and the structure of GalOS products will he also observed. All experiment steps will be carried out in the laboratory consisting of (a) synthesis of homoGalOS using h-galactosidases at various concentrations (20%-50% w/v) of galactose or lactose and at various pH (6.0 —7.0); (h) synthesis of heteroGalOS with galactose as a donor and various acceptors (glucose, mannose, maltose, and sucrose) in the ratio of I : I using b-galactosidases; (c) determination of the amount of GalOS produced; and (d) determination of the structure of GalOS The experimental results showed that all enzymes were potential catalysts for the synthesis of GalOS Reaction time significantly affected the amount of GalOS produced, where the exporiential production occurred at the first 6 hours of incubation, and then it gradually increased to reach equilibrium after 24 hours incubation. The production of GalOS increased with the concentration of galactose or lactose up to 50% and then decreased when the concentration of lactose or galactose was higher than 50%. The synthesis reaction was not significantly affected by changing the pH from 6.0 to 7.0. The structure of homoGalOS and heteroGalOS consisted of various h-galactosidic linkages (b- I ,3-; h-I, 4-, and b- I ,6) clearly explaining that A. oryzae b-galactosidase was a non linkage-specific enzyme. The GalOS with b(I-4)-galactosidic were predominantly produced using b(I-4)-galactosidase from Bacillus circulans thus explaining that this enzyme is more specific than the enzyme from A. oryzae